Hitler : 1936-1945 / Ian Kershaw ; traducción de José Manuel Álvarez Flórez - Álvarez Flórez, José Manuel; Kershaw, Ian (Atalaya; 55)
1° ed. de 2000 y 3° ed. de 2000 | Bibliografía: p. 1011-1050. Índices